Shiga toxin type-2 (Stx2) induces glutamate release via phosphoinositide 3-kinase (PI3K) pathway in murine neurons - Obata, Fumiko; Hippler, Lauren M.; Saha, Progyaparamita; Jandhyala, Dakshina M.; Latinovic, Olga (Frontiers in Molecular Neuroscience, 2015)
Shiga toxin-producing Escherichia coli (STEC) can cause central nervous system (CNS) damage resulting in paralysis, seizures, and coma. The key STEC virulence factors associated with systemic illness resulting in CNS impairment are Shiga toxins (Stx). While neurons express the Stx receptor globotriaosylceramide (Gb3) in vivo, direct toxicity to neurons by Stx has not been studied. We used murine neonatal neuron cultures to study the interaction of Shiga toxin type 2 (Stx2) with cell surface expressed Gb3. Single molecule imaging three dimensional STochastic Optical Reconstruction Microscopy - Total Internal Reflection Fluorescence (3D STORM-TIRF) allowed visualization and quantification of Stx2-Gb3 interactions. Furthermore, we demonstrate that Stx2 increases neuronal cytosolic Ca2+, and NMDA-receptor inhibition blocks Stx2-induced Ca2+ influx, suggesting that Stx2-mediates glutamate release. Phosphoinositide 3-kinase (PI3K)-specific inhibition by Wortmannin reduces Stx2-induced intracellular Ca2+ indicating that the PI3K signaling pathway may be involved in Stx2-associated glutamate release, and that these pathways may contribute to CNS impairment associated with STEC infection.